2001
DOI: 10.1093/carcin/22.8.1155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the garlic compound diallyl disulfide on the metabolism, adherence and cell cycle of HT-29 colon carcinoma cells: evidence of sensitive and resistant sub-populations

Abstract: Diallyl disulfide (DADS) is a major organosulphur compound present in garlic with an anti-mitotic potential against colon neoplastic lesions in vivo and colon tumour cell growth in vitro. Using the human colon adenocarcinoma HT-29 Glc(-/+) cell line we identified sub-populations of tumoural cells with markedly different characteristics in terms of metabolic capacities, adhesion properties and distribution in the cell cycle phases. After 1 and 2 days treatment with 100 microM DADS HT-29 cells were largely relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…More recent studies including those from our laboratory have revealed that some naturally occurring OSC analogues can inhibit proliferation of cultured cancer cells by causing apoptosis and/or cell cycle arrest (Sundaram and Milner, 1996;Milner, 1998, 2000;Nakagawa et al, 2001;Robert et al, 2001;Shirin et al, 2001;Kwon et al, 2002;Li and Lu, 2002;Filomeni et al, 2003;Xiao et al, 2003;Lan and Lu, 2004;Xiao et al, 2004). Milner and co-workers were the first to report apoptosis induction and cell cycle arrest by DADS in human colon cancer cells (Sundaram and Milner, 1996;Milner, 1998, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…More recent studies including those from our laboratory have revealed that some naturally occurring OSC analogues can inhibit proliferation of cultured cancer cells by causing apoptosis and/or cell cycle arrest (Sundaram and Milner, 1996;Milner, 1998, 2000;Nakagawa et al, 2001;Robert et al, 2001;Shirin et al, 2001;Kwon et al, 2002;Li and Lu, 2002;Filomeni et al, 2003;Xiao et al, 2003;Lan and Lu, 2004;Xiao et al, 2004). Milner and co-workers were the first to report apoptosis induction and cell cycle arrest by DADS in human colon cancer cells (Sundaram and Milner, 1996;Milner, 1998, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Similar to the majority of plant products, DADS exerts anticarcinogenic activity in certain types of cancer, including human breast (9), colon (10,11) and prostate cancer (8,12), as well as hepatoma cells (13). It has been observed that DADS, as an effective modulator of protein kinases/phosphatases, inhibits the initiation and promotion phases of cancer (5).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that some OSC analogues can inhibit proliferation of cultured cancer cells by causing apoptosis and/or cell cycle arrest (Sundaram and Milner, 1996;Milner, 1998, 2001;Nakagawa et al, 2001;Robert et al, 2001;Shirin et al, 2001;Kwon et al, 2002;Filomeni et al, 2003;Xiao et al, 2003a). Milner and co-workers were the first to report apoptosis induction by DADS in HCT-15 human colon cancer cells, which correlated positively with an increase in intracellular free calcium levels (Sundaram and Milner, 1996).…”
Section: Introductionmentioning
confidence: 99%